Mechanism and analytical models for the gas distribution on the SiC foam monolithic tray. Issue 12 (18th July 2015) - Li, Hong; Fu, Long; Li, Xingang; Gao, Xin
Abstract : Silicon carbide (SiC) foam material has been applied as monolithic tray for distillation column in our previous study. A systematic understanding of the gas distribution process on the foam tray should help to the design of commercial application. In this article, local gas holdup distribution and bubble size distribution are used to measure the gas distribution. The local gas holdup is tested by the conductive probe and the number of test point is counted in different local gas holdup. The bubbles are captured by the high‐speed camera to measure the bubble size. Bubble size is calculated as ellipsoidal bubble and counted with different pore sizes. Furthermore, a three‐stage process model is put forward to explain the uneven distribution of gas phase, and verified by the experimental values. The results show that the structure and the thickness of SiC foam is the decisive factor for the gas distribution performance. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4509–4516, 2015